Combining Oxoammonium Cation Mediated Oxidation and Photoredox Catalysis for the Conversion of Aldehydes into Nitriles - Nandi, Jyoti; Witko, Mason L.; Leadbeater, Nicholas E. (Synlett, 2018)
A method to oxidize aromatic aldehydes to nitriles has been developed. It involves a dual catalytic system of 4-acetamido-TEMPO and visible-light photoredox catalysis. The reaction is performed using ammonium persulfate as both the terminal oxidant and nitrogen source.
Keywords: photooxidation; nitriles; ammonium persulfate; oxoammonium cations; visible light